Cell stretchers and the LINC complex in mechanotransduction - Abdulghani A. Khilan (17316922) (2021)
How cells respond to mechanical forces from the surrounding environment is critical for cell survival and function. The LINC complex is a central component in the mechanotransduction pathway that transmits mechanical information from the cell surface to the nucleus. Through LINC complex functionality, the nucleus is able to respond to mechanical stress by altering nuclear structure, chromatin organization, and gene expression. The use of specialized devices that apply mechanical strain to cells have been central to investigating how mechanotransduction occurs, how cells respond to mechanical stress, and the role of the LINC complexes in these processes. A large variety of designs have been reported for these devices, with the most common type being cell stretchers. Here we highlight some of the salient features of cell stretchers and suggest some key parameters that should be considered when using these devices. We provide a brief overview of how the LINC complexes contribute to the cellular responses to mechanical strain. And finally, we suggest that stretchers may be a useful tool to study aging. Other Information Published in: Archives of Biochemistry and Biophysics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.abb.2021.108829